Peripheral refraction and aberrations in myopic eyes after small-incision lenticule extraction (SMILE) surgery - Lin Zhang; Yan Wang; Xinheng Zhao; Tong Cui (Scientific Reports)
Abstract To investigate peripheral refraction and aberrations in myopic eyes after small-incision lenticule extraction (SMILE) surgery and to understand the relationship between visual symptoms and wide-field wavefront aberrations. A total of 28 patients with myopia and myopic astigmatism underwent SMILE surgery. Peripheral refraction and aberrations were measured both before and six months after surgery using a modified wide-field Shack–Hartmann wavefront (SHWS) sensor-based aberrometer. The peripheral refraction and aberrations from the axis (0°) to (15°) in both the horizontal and vertical directions were measured. A visual questionnaire was administered to assess visual quality before and six months after surgery. Post-surgery, peripheral relative refraction exhibited reduced hyperopia. The spherical aberration $${Z}_{4}^{0}$$ changed from 0.12 ± 0.11 μm before surgery to 0.24 ± 0.14 μm (t = 20.047, P = 0.000) after surgery on the optical axis(0°). Post-surgery, the spatial pattern of spherical aberration remained constant. Greater variability of peripheral aberrations was observed in the direction of the horizontal retina than in the vertical axis after surgery. Horizontal coma significantly increased after surgery and appeared to be more variable in the direction of the surperior region. $${Z}_{3}^{-1}$$ shifted from -0.03 ± 0.16 μm preoperatively to -0.12 ± 0.18 μm postoperatively (t = 0.580, P = 0.573), $${Z}_{3}^{1}$$ changed from 0.03 ± 0.22μm preoperatively to 0.37 ± 0.35 μm postoperatively (t =  − 3.780, P = 0.003) on the central axis. The majority of patients were satisfied with the postoperative daytime vision; there was no significant deterioration in nighttime visual symptoms compared to preoperative levels. Our study demonstrated that SMILE significantly reduced peripheral refraction in myopic eyes, however with increased asymmetry along the vertical axis. Notably, the relationship between nighttime visual symptoms and large-field aberrations was not found to be significant.